30 years later. Contributions from the SENA Technical Unit - Gutierrez Carrión, Lucila
This article presents some reflections on the publication discussed by the Technical Unit of SENA in 1985. In addition to being a resource that presented in detail the normative references for the procedures in the management of the SENA’s Integral Professional Training, the Technical Unit also registered the fundamental guidelines of pedagogical policy which, although they have had some modification, are still valid. The specific nature of vocational training, curricular processes, teacher training, among others, are aspects that represent the institutional mission spirit.